Ultrathin rhodium nanosheet–gold nanowire nanocomposites for alkaline methanol oxidation reaction. Issue 79 (15th September 2022) - Sun, Bin; Wang, Zhe; Yuan, Zi-Han; Ding, Yu; Li, Fu-Min; Zhao, Guang-Tao; Li, Dong-Sheng; Li, Xi-Fei; Chen, Yu
Abstract : Electrostatically assembled ultrathin rhodium nanosheet–gold nanowire nanocomposites (Rh–Au CNSs) were used as an advanced electrocatalyst for the methanol oxidation reaction, which revealed a mass activity of 355 mA mgRh −1 at 0.607 V potential. Abstract : Electrostatically assembled ultrathin rhodium nanosheet–gold nanowire nanocomposites (Rh–Au CNSs) were used as an advanced electrocatalyst for the methanol oxidation reaction, which revealed a mass activity of 355 mA mgRh −1 at 0.607 V potential, much higher than single metal Rh nanosheets (273 mA mgRh −1 ) and commercial Rh nanoparticles (165 mA mgRh −1 ).